The impacts of online advertising on consumer attitudes / Mariana Dasiry - Dasiry, Mariana (2016)
The research was undertaken at UiTM Sarawak (Samarahan Campus) and Kota Samarahans’ areas to conduct a preliminary study on the impacts of online advertising on consumer attitudes. The respondents were randomly selected from Bachelor Degree students of Marketing programme and general public that available in Kota Samarahans’ areas. The purpose of this Study is to identify the key factors of online advertising that influencing consumer attitudes and to examine the relationship between online advertising arid consumer attitudes.